Recent advances in genomics assisted breeding for drought stress tolerance in major cereals - Wani, Shabir Hussain; Choudhary, Jeet R; Choudhary, Mukesh; Rana, Maneet; Gosal, Satbir S (Journal of Cereal Research, 2025)
Drought is one of the foremost threats for global cereal crop production with looming risks due to changing climatic scenarios. Among major cereals, rice wheat and maize are commonly grown worldwide for their importance as staple food as well as significance in fulfilling the nutritional requirements among the escalating human population. Drought being a complex trait is difficult to manage through conventional breeding approaches therefore, recent advances in genomics tools has resulted in précised and targeted identification of mechanisms underlying drought stress tolerance in cereals. Further, combination of customary breeding advances with the recent high throughput genomics technologies resulted in the popularization of genomics assisted breeding. There are various marker-assisted breeding (MAB) strategies to transfer or introgress trait of interest; these include marker-assisted selection (MAS); marker-assisted introgression (MAI), MA-backcrossing (MABC), MA-recurrent selection (MARS), MA-gene pyramiding (MAGP); genome-wide selection (GWS) and genomic selection (GS). In this review, recent advances for achieving drought stress tolerance in major cereals using genomics assisted breeding (GAB) has been discussed . We begin with the genetics of drought stress traits, MAB for abiotic stress tolerance with successful examples of mapped genomic regions for drought stress tolerance in rice, wheat and maize, respectively and finally MAI of genomic regions for improvement of drought tolerance in cereals. Further, in addition to MAB, genomic selection, an advanced molecular breeding technology, have pronounced potential to improve multiple traits simultaneously including drought tolerance in cereals.DOI.10.25174/2582-2675/2020/100821